치과기공실 공기중 및 치과기공사의 혈액, 요중 중금속 함량에 관한 연구 - 차성수 (연세대학교 보건대학원, 1988)
[한글] 오늘날 치과용 금속재료로써 니켈-크롬합금과 크롬-코발트합금 등은 관교의치와 국부의치 제작용으로 다량 사용되고있고, 카드뮴은 도재기공의 피복금관의 제작에 사용되고 있다. 그러나 대부분의 치과기공실이 협소하고 밀폐화된 경향이 있어 금속의 분진이나 흠에 장기간 노출되어 작업환경 위생관리에 많은 관심이 야기되고 있다. 그러나 이러한 특수환경에서 근무하는 치과기공사에 있어서 공기중 및 체내 중금속 농도에 관한 연구문헌이 우리나라에는 거의 없는 실정이다. 따라서 본 연구는 치과기공사들이 근무하는 작업장의 공기중 카드뮴, 니켈, 크롬의 농도를 조사하고 이들의 혈액 및 요중 카드뮴, 니켈, 크롬농도를 측정하여 그 성적을 근속년수, 작업부서, 업무내용, 흡연여부등 제반요인에 따라 비교 분석함에 목적이 있다. 연구 방법은 부산지역에 거주하는 남자치과기공사 48명과 대조군인 사무직 근로자 72명을 대상으로 이들의 혈액 및 요중 카드뮴, 니켈, 크롬농도와 이들의 작업장 공기중 중금속 농도를 1987년 6월 1일부터 1987년 9월 30일까지 4개월간 조사분석한바 다음과 같은 결론을 얻었다. 1. 작업부서별 공기중 카드뮴농도는 도재기공부서에서 기하평균 0.0087±0.0016mg/m**3로 가장 높았으며, 니켈농도는 관교의치기공부서에서 0.4253±0.O052mg/M**3로 가장 높았 으며, 크롬농도는 국부의치기공부서에서 0.1063±0.O024mg/m**3로 가장 높았다. 2. 치과기공사의 혈액중 카드뮴, 니켈, 크롬의 농도는 1.92±1.23㎍/100ml, 63.02±34.25㎍/10oml, 2.17±1.5㎍/100ml이었고 일반사무직 근로자인 대조군은 각각 0.90±0.73㎍/100ml, 45.64±35.23㎍/100ml, 1.41±0.72㎍/100ml이었다. 또한 치과기공사의 요중 카드뮴, 니켈, 크롬의 농도는 1.95±1.90㎍/ℓ, 48.53±38.83㎍/ℓ, 13.54±10.25㎍/ℓ이었고 대조군은 각각 1.32±0.93㎍/ℓ, 20.24±15.35㎍/ℓ, 7. 82±6.83㎍/ℓ이었다. 따라서 치과기공사의 혈액 및 요중 카드뮴, 니켈, 크롬농도는 일반사무직 근로자인 대조군보다 각각 높았으며 유의한 차이가 있었다. 3. 작업부서에 따른 혈액중 카드뮴농도는 도재기공부서에서 2.53±1.08㎍/100ml로 가장 높았으며, 혈액중 크롬농도는 국부의치기공부서에서 3.60±1.02㎍/100ml로 가장 높았고, 요중 카드뮴농도는 도재기공부서에서 3.41±3.15㎍/ℓ로써 가장 높았으며, 작업부서에 따라 각각 유의한 차이가 있었다. 4. 금속삭제 및 연마 작업자군의 요중 카드뮴농도는 2.64±2.41㎍/ℓ로써 wax조각 및 총의치를 제작하는 비금속 취급 작업자군의 1.39±1.18㎍/ℓ보다 높았다. 5. 흡연자군의 혈액중 크롬의 농도는 2.46±1.54㎍/100ml로써 비흡연자군의 1.54±1.25㎍/100ml 보다 높았다. 6. 근속년수에 따른 혈액 및 요중 카드뮴, 니켈, 크롬농도는 각각 유의한 차이가 없었다. 7. 혈액중 니켈농도와 혈액중 크롬농도사이의 상관계수는 0.605로 가장 높았으며 비교적 높은 상관관계가 있었다. 이와같은 결과에서 치과기공실의 각 작업부서별 공기중 카드뮴, 니켈, 크롬의 농도는 주로 취급하는 중금속 물질의 종류 및 량에 따라 증가하는 경향을 보였으며 치과기공사의 혈액 및 요중 중금속농도는 공기중 중금속농도가 높은부서에서 높게 나타나는 양상을 보 였다. 이에 치과기공실에 있어서 국소배기 시설등과 같은 작업환경관리에 많은 관심이 요구되며, 향후 이들의 체내 중금속에 대한 생물학적 모니터링이 지속적으로 수행되어 건강장해에 대한 예방관리 측면에서 계속적인 연구가 요망된다. A Study on the Heavy Metals Concentrations in the Air of the Dental Laboratories, in the Blood and Urine of Dental Laboratory Technicians Sung Soo Cha Graduate School of Health Science and Management, Yonsei University (Directed by Professor Chong Youl Kim D.D.S.) The purpose of this study was to determine the concentration of cadmium, nickel and chromiun in the air of the work-place, blood of and urine of workers and compare the level of those heavy metals by the duration of work, workplace, process of work, smoking and other factors. In this study, 48 male dental laboratory technicians and 72 office workers as the control group were subjected. The concentration of cadmium, nickel and chromium in their blood and urine, and that of heavy metals in the air of their work-rooms were examined and analysed from June 1,1987 to September 30, 1987. The results were as follows: 1. The concentration of cadmium in the air was the highest in the porcelain part, 0.0087±0.0016㎎/㎥, that of nickel wart the highest in the crown bridge part, 0.4253±0.0052㎎/㎥, and that of chromium was the highest in the partial denture part, 0.1063±0.0024 ㎎/㎥. 2. Cadmium, nickel and chromium concentraions in the blood and urine of dental laboratory technicians were higher than that in the office workers'. Especially the concentration of cadmium in the blood (1.92±1.23㎍/100ml) of the dental laboratory techician was about two times as high as that in the office workers' (0.90± 0.73㎍/100ml), and the concentration of nickel in the urine (48.53±38.83㎍/ℓ ) of the dental laboratory technician was about two times as high as that in the office worker's (20.24±15.37㎍/ℓ). 3. There was no difference in the concentration of cadmium, nickel and chromium in the blood art urine with a longer duration of work. 4. The concentration of cadmium and chromium in the blood and urine differed significantly depending upon the place of work. The concentration of cadmium was the highest in the blood of dental laboratory technicians working in the porcelain part marking at 2.53±1.08㎍/100ml. The chromium level was the heighest in the blood of partial denture part workers with a concentration of 3.60±1.02㎍/100ml. Concerning the level of cadmium in urine, it was the highest in the porcelain part workers with a concentration of 3.41±3.15㎍/ℓ. 5. The concentration of cadmium in the urine of metal trimming and polishing group (2.64±2.41㎍/ℓ) was higher than that of non-metal trimming and polishing group (1.39±1.18㎍/ℓ). 6. The concentration of chromiun in the blood of smoking group(2.46±1.54 ㎍/100ml) was higher than that of non-smoking group(1.54±1.25㎍/100ml). 7. The height positive correlation coefficient was shown between the concentration of nickel and chromium in the blood among the all correlations coefficients between 3 metals (Cd, Ni, Cr) in the blood and those in urine. The correlation coefficient was relatively high(r=0.605, p<0.01). In general, the higher the concentration of heavy metals in the air of work places the higher the concentration of them in the blood and urine of workers. Therefore, more attention should be paid to the working environment of dental laboratory workers. Furthermore, continuous biological monitoring and further research are required for an efficient health management for dental laboratory workers. [영문] The purpose of this study was to determine the concentration of cadmium, nickel and chromiun in the air of the work-place, blood of and urine of workers and compare the level of those heavy metals by the duration of work, workplace, process of work, smoking and other factors. In this study, 48 male dental laboratory technicians and 72 office workers as the control group were subjected. The concentration of cadmium, nickel and chromium in their blood and urine, and that of heavy metals in the air of their work-rooms were examined and analysed from June 1,1987 to September 30, 1987. The results were as follows: 1. The concentration of cadmium in the air was the highest in the porcelain part, 0.0087±0.0016㎎/㎥, that of nickel wart the highest in the crown bridge part, 0.4253±0.0052㎎/㎥, and that of chromium was the highest in the partial denture part, 0.1063±0.0024 ㎎/㎥. 2. Cadmium, nickel and chromium concentraions in the blood and urine of dental laboratory technicians were higher than that in the office workers'. Especially the concentration of cadmium in the blood (1.92±1.23㎍/100ml) of the dental laboratory techician was about two times as high as that in the office workers' (0.90± 0.73㎍/100ml), and the concentration of nickel in the urine (48.53±38.83㎍/ℓ ) of the dental laboratory technician was about two times as high as that in the office worker's (20.24±15.37㎍/ℓ). 3. There was no difference in the concentration of cadmium, nickel and chromium in the blood art urine with a longer duration of work. 4. The concentration of cadmium and chromium in the blood and urine differed significantly depending upon the place of work. The concentration of cadmium was the highest in the blood of dental laboratory technicians working in the porcelain part marking at 2.53±1.08㎍/100ml. The chromium level was the heighest in the blood of partial denture part workers with a concentration of 3.60±1.02㎍/100ml. Concerning the level of cadmium in urine, it was the highest in the porcelain part workers with a concentration of 3.41±3.15㎍/ℓ. 5. The concentration of cadmium in the urine of metal trimming and polishing group (2.64±2.41㎍/ℓ) was higher than that of non-metal trimming and polishing group (1.39±1.18㎍/ℓ). 6. The concentration of chromiun in the blood of smoking group(2.46±1.54 ㎍/100ml) was higher than that of non-smoking group(1.54±1.25㎍/100ml). 7. The height positive correlation coefficient was shown between the concentration of nickel and chromium in the blood among the all correlations coefficients between 3 metals (Cd, Ni, Cr) in the blood and those in urine. The correlation coefficient was relatively high(r=0.605, p<0.01). In general, the higher the concentration of heavy metals in the air of work places the higher the concentration of them in the blood and urine of workers. Therefore, more attention should be paid to the working environment of dental laboratory workers. Furthermore, continuous biological monitoring and further research are required for an efficient health management for dental laboratory workers.
보건학과/석사